Materialisation in art & design (MAD) - Montalti, Maurizio; Verkerk, Herman (Sandberg series, 2019)
When making things without prior knowledge of "the material," how should such naive and potentially brutal behavior be interpreted, and what does it represent and generate? The temporary master Materialisation in Art & Design (MAD) investigated this question through multiple ways of working, on a permanent quest to (re)establish our relationship with "material" on both a personal and a societal level. This book reflects on the experiences generated through the lens of MAD. With contributions from the program directors, MAD alumni, and experts in the field, it examines the position of the workshop within the art academy. By implication, it also reflects on the need for collective creative output in an increasingly individualized society, questioning the traditional frameworks of art and design education.